Remembrance of things past: non-equilibrium effects and the evolution of critical fluctuations near the QCD critical point - Mukherjee, Swagato; Venugopalan, Raju; Yin, Yi (Nuclear physics. A, Nuclear and hadronic physics, 2016)
We report on recent progress in the study of the evolution of non-Gaussian cumulants of critical fluctuations. We explore the implications of non-equilibrium effects on the search for the QCD critical point.